Optimizing communication strategies and designing a comprehensive program to facilitate cascade testing for familial hypercholesterolemia - Gemme Campbell-Salome; Laney K. Jones; Nicole L. Walters; Kelly M. Morgan; Andrew Brangan; Ilene G. Ladd; Mary P. McGowan; Katherine Wilemon; Tara J. Schmidlen; Emilie Simmons; Marci L. B. Schwartz; Megan N. McMinn; et al. (BMC, 2023)
Abstract Background This project aimed to optimize communication strategies to support family communication about familial hypercholesterolemia (FH) and improve cascade testing uptake among at-risk relatives. Individuals and families with FH provided feedback on multiple strategies including: a family letter, digital tools, and direct contact. Methods Feedback from participants was collected via dyadic interviews (n = 11) and surveys (n = 98) on communication strategies and their proposed implementation to improve cascade testing uptake. We conducted a thematic analysis to identify how to optimize each strategy. We categorized optimizations and their implementation within the project's healthcare system using a Traffic Light approach. Results Thematic analysis resulted in four distinct suggested optimizations for each communication strategy and seven suggested optimizations that were suitable across all strategies. Four suggestions for developing a comprehensive cascade testing program, which would offer all optimized communication strategies also emerged. All optimized suggestions coded green (n = 21) were incorporated. Suggestions coded yellow (n = 12) were partially incorporated. Only two suggestions were coded red and could not be incorporated. Conclusions This project demonstrates how to collect and analyze stakeholder feedback for program design. We identified feasible suggested optimizations, resulting in communication strategies that are patient-informed and patient-centered. Optimized strategies were implemented in a comprehensive cascade testing program.